2015
DOI: 10.1370/afm.1734
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Imaging for Tailored Treatment of Patients With Acute Shoulder Pain

Abstract: PURPOSE:The objective of this study was to assess the frequencies of ultrasound findings in patients with acute rotator cuff disorders in family medicine. METHODS:In a prospective observational study, 129 patients aged 18 to 65 years with acute shoulder pain in whom the family physician suspected rotator cuff disease underwent ultrasound imaging. RESULTS:Rotator cuff disease was present in 81% of the patients, and 50% of them had multiple disorders. Calcific tendonitis was the most frequently diagnosed specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 6 publications
3
16
0
Order By: Relevance
“…21 26 53 If GPs still consider ultrasound imaging, it might be used preferentially in patients aged 40 years or older, as over 90% of shoulder pain patients in this age group have a subacromial disorder, compared to a much lower prevalence in younger age groups. 25 In patients with persistent pain, ultrasound imaging may yield a more specific diagnosis, provide a rationale for further treatment and inform patients about the prognosis of their disorder. For daily practice, it is important that ultrasound findings are considered in the clinical context, as asymptomatic findings may be detected.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…21 26 53 If GPs still consider ultrasound imaging, it might be used preferentially in patients aged 40 years or older, as over 90% of shoulder pain patients in this age group have a subacromial disorder, compared to a much lower prevalence in younger age groups. 25 In patients with persistent pain, ultrasound imaging may yield a more specific diagnosis, provide a rationale for further treatment and inform patients about the prognosis of their disorder. For daily practice, it is important that ultrasound findings are considered in the clinical context, as asymptomatic findings may be detected.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…[22][23][24] Moreover, the full spectrum of subacromial disorders is observed in patients with shoulder pain presenting in general practice. [25][26][27] For each of these disorders, evidence-based treatments are available. 3 28 29 This implies that stratification of patients into diagnostic subgroups potentially allows for more tailored treatment than currently applied.…”
Section: Introductionmentioning
confidence: 99%
“…The rotator cuff is a natural reduction of the muscle-tendon unit in old adults [7]. Many of the patients with pain in the shoulder are treated under medicine by orthopedic surgeons [8,9] because 30–70% of painful shoulders patients are related cases of rotator cuff disorders [7]. Physical tests like the external rotation lag test and positive painful arc test [10] are utilized to assess the rotator-cuff syndrome but usually insufficient to predict the morphology and size of rotator-cuff [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective observational study under 240 patients who were referred by GPs to make a DUS, concluded that in most cases there was a calcific tendonitis (29%), a tendinopathy in 11% of cases and a full-thickness tear in 8% (Ottenheijm et al, 2010). A prospective study where patients with acute shoulder pain were referred to a radiologist for DUS also showed calcific tendonitis to be the most frequently observed pathology (50.4%) followed by tendinopathy (28.7%) and full thickness tears (3.1%) (Ottenheijm et al, 2015). A systematic review with secondary care studies, showed that tendinopathy (30-39%) and full thickness tears (24-70%) were the most observed disorders (Ottenheijm et al, 2010).…”
Section: Comparison With the Literaturementioning
confidence: 99%